18FDG PET and PET‐CT for the detection of bone metastases in patients with head and neck cancer. A meta‐analysis. Issue 6 (24th June 2013) - Yi, Xuelian; Fan, Min; Liu, Yilin; Zhang, Hongting; Liu, Shixi
Abstract Introduction We performed a meta‐analysis to evaluate 18FDG PET/PET‐CT for the detection of bone metastases in patients with head and neck cancer. Methods We calculated sensitivities, specificities, likelihood ratios, and constructed summary receiver operating characteristic curves for PET and PET‐CT, respectively. We also compared the performance of PET/PET‐CT with that of bone scintigraphy by analysing studies that had also used bone scintigraphy on the same patients. Results Across 9 PET studies (1621 patients) and 10 PET‐CT studies (1291 patients), sensitivity and specificity of PET were 0.81 and 0.99, and of PET‐CT were 0.89 and 0.99, respectively. In 5 comparative studies (1184 patients), sensitivity and specificity of PET/PET‐CT were 0.85 and 0.98, and of bone scintigraphy were 0.55 and 0.98, respectively. Conclusions 18FDG PET and PET‐CT have high sensitivity and accuracy for the detection of bone metastasis in patients with head and neck cancer.